Analisis Teori Belajar dalam Pemanfaatan Media Pembelajaran - Ahmad Faiz Ritonga; Suci Setiyani Putri; Nasywa Aulia Putri Efendi; Zaskia Alya Nuraini; Hesti Kusumaningrum (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This study is motivated by the importance of utilizing instructional media that is not only visually appealing but also grounded in solid learning theories. A common problem is that instructional media are often used without proper alignment with underlying learning theories, resulting in suboptimal learning outcomes. This study aims to analyze the relationship between learning theories—behaviorism, cognitivism, and constructivism—and the use of instructional media. The research employs a qualitative approach using library research with content analysis techniques on relevant academic literature. The results indicate that each learning theory has distinct characteristics in the use of instructional media: behaviorism emphasizes drill and reinforcement-based media, cognitivism focuses on structured and visual media, and constructivism promotes interactive and contextual media. Furthermore, the integration of these three theories in instructional media use enhances learning effectiveness and student engagement. Therefore, the selection of instructional media should be aligned with appropriate learning theories to create meaningful and effective learning processes.